2021
DOI: 10.1002/mus.27461
|View full text |Cite
|
Sign up to set email alerts
|

Acute‐onset polyradiculoneuropathy after SARS‐CoV2 vaccine in the West and North Midlands, United Kingdom

Abstract: Introduction/Aims: We aimed to determine whether specific severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) vaccines may be associated with acute-onset polyradiculoneuropathy and if they may result in particular clinical presentations. Methods: We retrospectively reviewed records of all persons presenting with acuteonset polyradiculoneuropathy from January 1, 2021, to June 30, 2021, admitted to two Neuroscience centers, of the West and North Midlands, United Kingdom. We compared subjects with previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 20 publications
(40 reference statements)
3
23
0
Order By: Relevance
“…The authors found a 2.6‐fold increase in number of admissions for GBS during the study period, compared to the same period in the previous 3 years 237 . Patients presenting with GBS after AstraZeneca vaccine had more frequent facial and bulbar involvement than the historical cases, and more commonly they had the bifacial weakness and distal paresthesia GBS variant, similar to the above‐mentioned reports 237‐239 …”
Section: Methodssupporting
confidence: 75%
See 2 more Smart Citations
“…The authors found a 2.6‐fold increase in number of admissions for GBS during the study period, compared to the same period in the previous 3 years 237 . Patients presenting with GBS after AstraZeneca vaccine had more frequent facial and bulbar involvement than the historical cases, and more commonly they had the bifacial weakness and distal paresthesia GBS variant, similar to the above‐mentioned reports 237‐239 …”
Section: Methodssupporting
confidence: 75%
“…226 A cohort study conducted from 1 January 2021 to 30 June 2021 at the Birmingham University Hospital, United Kingdom, compared 16 cases of GBS presenting within 4 weeks after the first COVID-19 vaccine (14 had received the AstraZeneca vaccine and the remaining two the Pfizer and Moderna vaccines) to a historical cohort of 114 consecutive GBS patients diagnosed between 2005 and 2019. 237 The authors found a 2.6-fold increase in number of admissions for GBS during the study period, compared to the same period in the previous 3 years. 237 Patients presenting with GBS after AstraZeneca vaccine had more frequent facial and bulbar involvement than the historical cases, and more commonly they had the bifacial weakness and distal paresthesia GBS variant, similar to the above-mentioned reports.…”
Section: Cov2s (Johnson and Johnsonmentioning
confidence: 75%
See 1 more Smart Citation
“…Fourteen of these had received the AZ vaccine, at a mean of 14.4 days prior to onset of symptoms. Four (25%) had a subsequent clinical course and electrophysiology meeting criteria for aCIDP, re-treated with IVIg, plasma exchange or corticosteroids [ 34 ]. These findings were supported by a recent review of the English National Immunisation Database of COVID-19 vaccination, which found an increased risk of hospital admission or death due to GBS 15–28 days following the first dose of the AZ vaccine, as well an increased risk of facial palsy in the same period.…”
Section: Discussionmentioning
confidence: 99%
“…Although lupus was not suspected initially, an antinuclear antibody panel and complement 3 and 4 concentrations were requested early after patient transfer to screen for an underlying etiology, particularly in view her family history with cases of SLE and (autoimmune) thyroid disease, respectively ( Table 1 ). Recent infection or vaccination, including COVID-19, a newly recognized trigger of GBS or GBS spectrum ( 23 25 ), were ruled out (SARS-CoV-2 vaccines were not yet available at the time).…”
Section: Discussionmentioning
confidence: 99%